Effect of nutriment from monoculture fermentation of Adasonia digitata seeds by Penicillium chrysogenum on haematology and functional endpoints of intra and extrahepatic tissues in rats - M.R. Adedayo; J.K. Akintunde; A. Sani; A. Boligon (Medicine in Microecology, 2023)
This current study is to identify the most appropriate dose against intra and extrahepatic toxic agents as well as hematosuppressive agent in rats. The animals were divided into six groups (n ​= ​10). Group 1 was placed on basal diet. Group II, III and IV were placed on a basal diets supplemented with 9.9%, 19.8% and 30%, respectively of MCF-ADSPC. Group V was placed on basal diet fed with unfermented Adasonia digitata seeds (UF-ADS) for 56 days. The results revealed 9.9% MCF-ADSPC as better dose to augment weight growth and total protein in rats. Similarly, MCF-ADSPC generated slight increase of WBC and centrophils count at lowest dose (9.9%) and highest dose (30%), respectively better than UF-ADS. The levels of PCV, RBC, haemoglobin, neutrophil, lymphocyte, eosinophils, basophils and monocytes showed no significant difference. Whereas, 19.8% MCF-ADSPC showed a better protection against hepatotoxicity, nephrotoxicity, intestinal mucosa, abnormal cholesterol level and splenomegaly in relation to 9.9%, 30% MCF-ADSPC and UF-ADS. Conclusively, MCF-ADSPC nutriment at 19.8% dose protected functional endpoints of intra and extrahepatic tissues than UF-ADS in a rat model.